Responses of soil respiration to phosphorus addition in global grasslands: A meta-analysis. (15th May 2022) - Lu, Xueyan; Wen, Lu; Sun, Haoyu; Fei, Tao; Liu, Huan; Ha, Sina; Tang, Shiming; Wang, Lixin
Abstract: Anthropogenic activities have increased phosphorus deposition and affected ecosystem carbon cycles. Although soil respiration (RS) is crucial in driving the global carbon cycle and regulating climate change, the general pattern of RS response to phosphorus addition remains unclear in global grassland ecosystems. By conducting a meta-analysis of 75 independent study sites from 41 studies worldwide, we explored the general patterns and associated drivers of RS to phosphorus addition in grassland ecosystems. Overall, results showed that different grassland ecosystem types have varied effects caused by phosphorus addition. Specifically, phosphorus addition significantly increased RS in overall global grasslands by 9.20%, by 12.78% in temperate grassland, and no significant effects on RS in other grassland ecosystems (alpine and tropical grasslands). The response of RS was significantly negatively correlated with total soil phosphorus and soil available phosphorus, indicating that phosphorus addition increased the availability of phosphorus in the soil and altered RS in grassland ecosystems. Moreover, different grassland ecosystem types influenced by climatic factors affected the respiratory processes of the grassland carbon cycle under phosphorus addition conditions. Meanwhile, different experimental variables had different effects on grassland RS. Specifically, phosphorus addition had a significant effect on RS in grassland ecosystems when the duration of fertilizer application was <5 years. Overall, our results suggest that future increases in global exogenous phosphorus loads will affect global carbon cycling, providing a framework for a better understanding of the dynamics and mechanisms of carbon cycling in grassland ecosystems under increased phosphorus inputs. Highlights: P addition significantly promoted soil respiration (RS) in temperate grassland (9.02%). Soil available P is one of the key environmental factors affecting RS in grassland under P addition. Grassland RS in different climate zones responded differently to P addition. P addition had a significant effect on RS in grassland when the duration of fertilizer application was <5 yr.